Investigating the Association of Criminal Behavior With Childhood Traumas, Impulsivity, and Dominant Temperaments in Bipolar I Disorder - Özsoy, Filiz; Taşcı, Gülay; Atmaca, Murad (Physicians Postgraduate Press Inc., 2022)
Objective: To examine impulsivity, dominant temperaments, and childhood trauma in patients with bipolar I disorder who committed crimes by comparing them with bipolar I patients with no criminal history and with healthy controls. Methods: A total of 144 subjects in 3 groups (62 criminal history bipolar patients, 40 non-criminal bipolar patients, and 42 controls) participated in this cross-sectional study. All participants completed the Childhood Trauma Questionnaire (CTQ), the Barratt Impulsiveness Scale (BIS-11), and the TEMPS-A (Temperament Evaluation of Memphis, Pisa, Paris, San Diego Autoquestionnaire). Subjects were enrolled in the study between April 1, 2019, and March 1, 2020. Results: The mean age was higher (P =.029) and education level lower (P =.045) among the criminal history bipolar patients than the other 2 groups. Of quantitative variables, physical abuse and emotional abuse subscales and total CTQ score were significantly higher in both patient groups compared to healthy controls (P <.001 for all scores). For dominant temperament, hyperthymic temperament scores of the criminal history bipolar group were higher than that of the control group (P <.001). Conclusions: Patients with bipolar I disorder were found to have experienced more childhood traumas, and the criminal history bipolar group and those who were admitted to prison had suffered more physical abuse. Hyperthymic temperament was dominant in bipolar I patients involved in crime. Taking into account the temperaments of bipolar I disorder in treatment plans and providing psychosocial support to these patients could help prevent violent behaviors and the possibility of crime. © 2022 Physicians Postgraduate Press, Inc.
Keywords: Adverse Childhood Experiences; Bipolar Disorder; Criminal Behavior; Cross-Sectional Studies; Humans; Impulsive Behavior; Personality Inventory; Surveys and Questionnaires; Temperament; adult; Article; Barratt Impulsiveness Scale; bipolar I disorder; childhood trauma; Childhood Trauma Questionnaire; controlled study; correlation analysis; criminal behavior; cross-sectional study; cyclothymia; depression; DSM-5; education; emotional abuse; hospitalization; human; impulsiveness; interview; major clinical study; marriage; outpatient; physical abuse; psychiatry; psychometry; sexual abuse; smoking; temperament; Temperament Evaluation of Memphis, Pisa, Paris and San Diego; Young Mania Rating Scale; bipolar disorder; criminal behavior; impulsiveness; personality test; psychology; questionnaire; temperament